Evaluation of adverse effects of long-term oral administration of carprofen, etodolac, flunixin meglumine, ketoprofen, and meloxicam in dogs - Luna, Stélio Pacca Loureiro [UNESP]; Basílio, Ana C. [UNESP]; Steagall, Paulo V.M. [UNESP]; Machado, Luciana P. [UNESP]; Moutinho, Flávia Q. [UNESP]; Takahira, Regina Kiomi [UNESP]; Brandão, Cláudia V.S. [UNESP] (American Veterinary Medical Association (AVMA), 2007)
Objective - To evaluate adverse effects of long-term oral administration of carprofen, etodolac, flunixin meglumine, ketoprofen, and meloxicam in dogs. Animals - 36 adult dogs. Procedures - Values for CBC, urinalysis, serum biochemical urinalyses, and occult blood in feces were investigated before and 7, 30, 60, and 90 days after daily oral administration (n = 6 dogs/group) of lactose (1 mg/kg, control treatment), etodolac (15 mg/kg), meloxicam (0.1 mg/kg), carprofen (4 mg/kg), and ketoprofen (2 mg/kg for 4 days, followed by 1 mg/kg daily thereafter) or flunixin (1 mg/kg for 3 days, with 4-day intervals). Gastroscopy was performed before and after the end of treatment. Results - For serum γ-glutamyltransferase activity, values were significantly increased at day 30 in dogs treated with lactose, etodolac, and meloxicam within groups. Bleeding time was significantly increased in dogs treated with carprofen at 30 and 90 days, compared with baseline. At 7 days, bleeding time was significantly longer in dogs treated with meloxicam, ketoprofen, and flunixin, compared with control dogs. Clotting time increased significantly in all groups except those treated with etodolac. At day 90, clotting time was significantly shorter in flunixin-treated dogs, compared with lactose-treated dogs. Gastric lesions were detected in all dogs treated with etodolac, ketoprofen, and flunixin, and 1 of 6 treated with carprofen. Conclusions and Clinical Relevance - Carprofen induced the lowest frequency of gastrointestinal adverse effects, followed by meloxicam. Monitoring for adverse effects should be considered when nonsteroidal anti-inflammatory drugs are used to treat dogs with chronic pain.
Keywords: carprofen; etodolac; etogesic; flunixin meglumine; gamma glutamyltransferase; ketoprofen; lactose; meloxicam; nonsteroid antiinflammatory agent; placebo; unclassified drug; bleeding time; blood cell count; blood clotting time; chronic pain; controlled study; drug dose reduction; female; gamma glutamyl transferase blood level; gastrointestinal disease; gastroscopy; long term care; nonhuman; occult blood; stomach lesion; urinalysis; Administration, Oral; Animals; Anti-Inflammatory Agents, Non-Steroidal; Blood Coagulation; Carbazoles; Clonixin; Dog Diseases; Dogs; Etodolac; Female; Ketoprofen; Stomach Diseases; Thiazines; Thiazoles; Time Factors; Animalia; Canis familiaris